The Quranic Text Approach: A Review of Watt and Crone’s Theses on the Emergence of Islam - Taufiqurrahman (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Montgomery Watt and Patricia Crone are two figures who are concerned to examine the emergence of Islam in Mecca, whether the trigger is socio-economic, trade, or socio-political, power. Watt states that Mecca from the beginning, which was already a center of pilgrimage, in the next process became an important trading center, giving birth to master traders. In the process, these conditions gave rise to Islam there. Crone, on the other hand, says it was Arab nationalism that determined the development of Islam in Mecca and the Arabian peninsula. This research will re-examine the two theses by trying to reveal through the approach of the Qur'anic texts, because according to the author, the revelation of the Qur'anic text cannot be separated from the situation that occurred at that time. This research is librabry research with documentation research techniques. Watt's thesis is closer to the truth that it was the trade factor that triggered the emergence of Islam. Crone's opinion is not in accordance with the text of the Qur'an. In Mecca there is no text that talks about political power, because Islam is still weak with few followers. Texts related to power only appeared after the hijrah, where it was needed to protect and defend the state of Medina from outside attacks, or even to expand power because of welfare needs, where financial resources were not found in Medina. [Montgomery Watt dan Patricia Crone adalah dua tokoh yang konsen mengkaji kemunculan Islam di Mekkah, apakah pemicunya adalah kekuasaan sosio-ekonomi, perdagangan, atau sosio-politik. Watt menyatakan bahwa Mekkah yang semula sudah menjadi pusat ziarah, pada proses selanjutnya menjadi pusat perdagangan penting sehingga melahirkan para pedagang ulung. Dalam perjalanannya, kondisi tersebut memunculkan Islam di sana. Crone, sebaliknya, mengatakan bahwa nasionalisme Arablah yang menentukan perkembangan Islam di Mekah dan semenanjung Arab. Penelitian ini akan mengkaji kembali kedua tesis tersebut dengan mencoba mengungkap melalui pendekatan teks Al-Qur’an, karena menurut penulis, turunnya teks Al-Qur’an tidak lepas dari situasi yang terjadi pada saat itu. Penelitian ini merupakan penelitian kepustakaan dengan teknik penelitian dokumentasi. Pendapat Watt lebih mendekati kebenaran bahwa faktor perdaganganlah yang memicu munculnya Islam. Pendapat Crone tersebut tidak sesuai dengan teks Al-Qur'an. Di Mekkah belum ada teks yang berbicara tentang kekuasaan politik, karena Islam masih lemah dengan pengikut yang sedikit. Teks-teks yang berkaitan dengan kekuasaan baru muncul setelah masa hijrah, dimana diperlukan untuk melindungi dan mempertahankan negara Madinah dari serangan luar, atau bahkan untuk memperluas kekuasaan karena kebutuhan kesejahteraan, dimana sumber daya finansial tidak terdapat di Madinah.]